Impact of the Credit Rating Agencies on the Financial Crisis 2007–2009 - Marciniak, Piotr (Annales. Etyka w Życiu Gospodarczym, 2015)
The paper presents some ethical aspects of the credit rating agencies (CRAs) market in the light of the latest economic crisis of 2008. A historical background is also shown and how the CRA market emerged. It is emphasised how the functioning of CRAs contributed to the outbreak of the crisis and what were the consequences of over- or underestimated rating grades. The downgrading of a country has a significant influence on the deterioration of the economic condition. Simultaneously, it afflicts the citizens, who have to pay for it e.g. with higher tax rates. It is believed that overestimated ratings lead to a speculative bubble, which ends up with the crisis. The paper indicates the problems connected with the way that CRAs operate and how they relate to business ethics. The fact that those institutions are profitprofile entities, which earn their income from clients, whose financial instruments are assessed, may bring about a conflict of interests. Moreover, it is outlined how the governmental policies of countries left CRAs without any particular control, which in the end was a significant factor, too. Finally, some potential solutions are discussed, and how the approach of CRA managers should change in order to prevent the market from similar situations in the future.